Quantitative genetics, molecular techniques and agronomic performance of provitamin a maize in sub-Saharan Africa - Badu-Apraku, Baffour; Fakorede, M.A.B.; Talabi, A.O.; Obeng-Bio, E.; Tchala, S.G.N.; Oyekale, S.A. (CAB International, 2020)
This chapter focuses on quantitative genetics, screening of germplasm collection at the International Institute of Tropical Agriculture, genetic diversity, genetic variation of provitamin A content in maize. Inheritance, heritability, genotype-by-environment for carotenoid content, population improvement, development of open-pollinated varieties were also discussed. Agronomic performance, stress tolerance, combining ability, heterosis were also conducted in sub-Saharan Africa. It may be concluded that maize in sub-Saharan Africa can be effectively subjected to genetic enhancement of provitamin A, along with other mineral components of the kernel and the plant traits for sustainable, high-quality food sufficiency to drastically reduce hunger and malnutrition.